Pencegahan Stunting melalui Kegiatan Penyuluhan kepada Masyarakat dalam Memperingati Hari Pangan Se-Dunia - Luise Handika; Adita Nafisa (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2025)
Commemorating World Food Day to promote a stunting-free nation and create a Healthy Indonesia 2045. Because one of the causes of stunting in early childhood is a lack of attention to health and food and nutritional intake during pregnancy, childbirth and post-natal periods, which affects health and child growth. In line with the 2020-2024 National Medium Term Development Plan (RPJMN), stunting is identified as a priority issue in health development. Therefore, the implementation of stunting counseling activities took place at the TBM Merdekata Gg RW Hall. Manunggal District. Klojen Malang City by inviting Polkesma Lecturers as competent speakers. This activity was carried out on October 28 2023 with the participation of 18 participants, consisting of mothers and children. The aim of this community service activity is to provide education to the public about stunting, with the hope of increasing awareness of the importance of children's health and growth, so that stunting can be prevented from an early age. The method used was stunting education to commemorate "World Food Day" with Polkesma lecturers as resource persons. The results of the activity show the enthusiasm of the community in participating in counseling, gaining knowledge about selecting high-quality food ingredients to support children's growth and health. It is hoped that after this activity, the community can apply the knowledge gained in their daily lives, so that efforts to prevent stunting can be realized.